A Descriptive Study On Strategies For Developing Reading Skill At The Second Year Of Islamic School MTsMuhammadiyah O2 Blora In 2011/2012 Academic Year - Iriyani, Sri (2012)
This research aims at describing the strategies for developing reading skills applied by the English teacher at the second year of Islamic School MTs Muhammadiyah 02 Blora and describing the problems faced by the English teacher in teaching reading at the second year of Islamic School MTs Muhammadiyah 02 Blora. The data are taken from observation and interview. While the data source are taken from all elements in teaching reading applied by the English teacher at the second year of Islamic School MTs Muhammadiyah 02 Blora. The methods of collecting the data are observation, documentation, and interview. After collecting and analyzing the data, the researcher described the result of the research. The result in this research is as follows: 1) the strategies for developing reading skill applied by the English teacher at the second year of Islamic School MTs Muhammadiyah 02 Blora consists of six steps: a) reviewing, b) predicting, c) skimming, d) scanning, e) guessing from the context, and f) paraphrasing. 2) the problems faced by the English teacher that consists of: a) difficulties in managing the students in the class, b) low motivation, and c) limited the time. Finally, the researcher concluded that strategies for developing reading skills applied by the teacher at the second year of Islamic School MTs Muhammadiyah 02 Blora is effective for the second year of Junior high school.